Evaluation of the efficacy of moringa oleifera seed powder on some physicochemical parameters in White Nile River water - ElGeed B. A , Awad; M.I, Abdelgadir; E.E, Elsadig; M .M, Hassan; F.I, Omer (International Journal of Medicine, 2023)
This study was aimed to evaluate the efficacy of Moringa oleifera seeds powder on purification of White Nile River water, during the dry season (March-April 2014). Water samples were collected from twelve different locations from the River at El duwaim city, on dimension 3.0 meters in front of the bank and 20 centimeters in depth. The physico-chemical parameters concentrations of water samples (pH, turbidity, electrical conductivity, total dissolved salts, total hardness, iron and chloride ions) were detected before treatment by Moringa oleifera seeds powder., various doses of Moringa seed powder (50, 100 and 150 mg/L) were added to water samples for a duration of one to two hours, then analyzed to detect the effects on that parameter. The results showed significant (p ≤ 0.05) decreased concentrations of all mentioned parameters, directly proportional with increasing dose and time respectively (except pH).